Research of an Algorithm for Smoothing of Digital Measurement Information in Systems of Dynamic Change (Texas Journal of Engineering and Technology, 2023)
This article discusses the construction of a smoothing algorithm for digital measurement information in dynamic change systems using the Kalman filter. Elimination of errors and errors in the sensors is carried out by a smoothing algorithm which is the most optimal method in this case. Adaptive anti-aliasing filters are used as an adaptive device